2021
DOI: 10.3390/antiox10071016
|View full text |Cite
|
Sign up to set email alerts
|

Extra Virgin Olive Oil Extracts Modulate the Inflammatory Ability of Murine Dendritic Cells Based on Their Polyphenols Pattern: Correlation between Chemical Composition and Biological Function

Abstract: Extra virgin olive oil (EVOO) represents one of the most important health-promoting foods whose antioxidant and anti-inflammatory activities are mainly associated to its polyphenols content. To date, studies exploring the effect of EVOO polyphenols on dendritic cells (DCs), acting as a crosstalk between the innate and the adaptive immune response, are scanty. Therefore, we studied the ability of three EVOO extracts (cv. Coratina, Cima di Mola/Coratina, and Casaliva), characterized by different polyphenols amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Six phenolic acids and derivatives were also revealed, namely quinic acid (4.1 μg mL −1 ), HyEDA (0.27 μg mL −1 ) and decarboxymethyl-elenolic acid derivative (1.55 μg mL −1 ), hydroxylated product of dialdhydic form of decarboxymethyl elenolic acid (3.3 μg mL −1 ), caffeic acid (1.9 μg mL −1 ) and p -coumaric acid (2.1 μg mL −1 ) on the basis of their [M–H] − ions as well as the presence of [M–H 2 O] − and [M–CO–2H 2 O] − in their fragmentation patterns [ 15 , 17 ]. The compounds at RT = 2.245 min and 2.470 min (having concentrations of 4.3 and 2.9 μg mL −1 , respectively) were two 3-hydroxytyrosol glucoside isomers because they showed the same [M–H] − at m / z 315 and similar MS/MS spectra characterized by two main fragment ions at m / z 153, which were formed through the loss of a glucose moiety and at m / z 123 corresponding to the subsequent loss of the CH 2 OH group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six phenolic acids and derivatives were also revealed, namely quinic acid (4.1 μg mL −1 ), HyEDA (0.27 μg mL −1 ) and decarboxymethyl-elenolic acid derivative (1.55 μg mL −1 ), hydroxylated product of dialdhydic form of decarboxymethyl elenolic acid (3.3 μg mL −1 ), caffeic acid (1.9 μg mL −1 ) and p -coumaric acid (2.1 μg mL −1 ) on the basis of their [M–H] − ions as well as the presence of [M–H 2 O] − and [M–CO–2H 2 O] − in their fragmentation patterns [ 15 , 17 ]. The compounds at RT = 2.245 min and 2.470 min (having concentrations of 4.3 and 2.9 μg mL −1 , respectively) were two 3-hydroxytyrosol glucoside isomers because they showed the same [M–H] − at m / z 315 and similar MS/MS spectra characterized by two main fragment ions at m / z 153, which were formed through the loss of a glucose moiety and at m / z 123 corresponding to the subsequent loss of the CH 2 OH group.…”
Section: Resultsmentioning
confidence: 99%
“…All data were processed using Mass Hunter Workstation software (version B.01.04; Agilent Technologies). UV absorption, retention times (RT), elution order and mass spectra (MS and MS/MS) were compared with those from pure standards (3-hydroxytyrosol, caffeic acid and p -coumaric acid) and/or matched with those already reported in the literature [ 15 , 16 , 17 ]. Then, the main revealed compounds were quantified by multiple reaction monitoring (MRM) as 3-hydroxytyrosol (R 2 = 0.99923).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study demonstrated a good correlation between the chemical characterization of EVOO extracts, a group of polyphenols (secoiridoids, lignans, and flavonoids), and their biological functions in terms of anti-inflammatory activity using cultured in vitro tissue. The specific OO polyphenol combination could be crucial for inducing the biological effects and, perhaps, reducing the risk of chronic inflammation that supports the development and the ever-increasing incidence of noncommunicable diseases nowadays [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, this happened without compromising the polyphenols' content of the EVOO, which not only did not decrease in any sample analyzed, but, depending on the variety and the ripeness index of the olives, could even increase compared to the measured values in the oils obtained using the malaxers. For instance, the compounds (namely, decarboxymethyl-oleuropein aglycone in open dialdehyde form, 77 vs. 74 mg/kg, decarboxymethyl-ligstroside aglycone in open dialdehyde form, 110 vs. 105 mg/kg, lignans, 98 vs. 84 mg/kg, and oleuropein and ligstroside aglycones, 27 vs. 25 mg/kg) quantified in EVOO from Coratina and Frantoio blend green olives by the HPLC-MS/MS method as described by De Santis et al, 2021 [32], were more concentrated in the Sono-Heat-Exchanger samples than the malaxer ones.…”
Section: Volatile Compoundsmentioning
confidence: 99%